A Review of Telemedicine in Pediatrics - K. Purrostami; H. Avary (Bihdād, 2015)
Extending in science technology and communication changes a lot in life and society has become. Medical science does not exclude the use of this technology is always a step ahead. Health services in the field of information technology is growing increasingly. In fact, to apply information technology to provide remote treatment and training and access to health information and appropriate access to health services is called telemedicine. This service can be used in various medical fields such as pediatric assessment. It is obvious that the current state of all medical practitioners in all health centers and small towns is not possible. The use of telemedicine techniques can lead to reduced health care costs, travel health, mortality and life expectancy is increasing. And since most children are at risk for various diseases So care needs to be fast and timely use of remote method is effective in the treatment of children in care.